Ethnic prejudice and discrimination in Europe - Zick, Andreas (Journal of social issues, 2008)
This article provides an introduction to research on European prejudice and discrimination. First, we list the distinctive characteristics of a European perspective and provide a short sketch of European immigration and ethnic groups. Europe has become a multicultural community. Nevertheless, public opinion and the continent's politics often do not reflect this empirical fact. Prejudice and discrimination directed at immigrants are a widespread phenomena across Europe. Several cross-European surveys support this conclusion, although theoretically driven surveys on prejudice and discrimination in Europe remain rare. Cross-European research studies classical and modern theories of prejudice and discrimination and attempts to uncover the psychological mechanisms that explain individual readiness to exclude ethnic groups. A brief sketch of recent European research is presented. This issue offers both important cross-national perspectives as well as needed comparisons with the more studied case of racial prejudice and discrimination in the United States.